Some theoretical issues of preparation of land for granting. (Journal of actual problems of jurisprudence, 2016)
This article discusses some theoretical issues of preparation of land for granted. In particular, the questions about the selection and the formation of the land plot are considered.
Keywords: the provision of land; selection; formation